Adenomatous polyposis coli (APC) membrane recruitment 3, a member of the APC membrane recruitment family of APC-binding proteins, is a positive regulator of Wnt-?-catenin signalling - Brauburger, Katharina; Akyildiz, Senem; Ruppert, Jan G.; Graeb, Michael; Bernkopf, Dominic; Hadjihannas, Michel; Behrens, Jürgen (Febs Journal, 2014)
The adenomatous polyposis coli (APC) membrane recruitment (Amer) family proteins Amer1/Wilms tumour gene on the X chromosome and Amer2 are binding partners of the APC tumour suppressor protein, and act as negative regulators in the Wnt signalling cascade. So far, nothing has been known about the third member of the family, Amer3. Here we show that Amer3 binds to the armadillo repeat domain of APC, similarly to Amer1 and Amer2. Amer3 also binds to the Wnt pathway regulator conductin/axin2. Furthermore, we identified Amer1 as binding partner of Amer3. Whereas Amer1 and Amer2 are linked to the plasma membrane by an N-terminal membrane localization domain, Amer3 lacks this domain. Amer3 localizes to the cytoplasm and nucleus of epithelial cells, and this is dependent on specific nuclear import and export sequences. Functionally, exogenous Amer3 enhances the expression of a ?-catenin/T-cell factor-dependent reporter gene, and knockdown of endogenous Amer3 reduces Wnt target gene expression in colorectal cancer cells. Thus, Amer3 acts as an activator of Wnt signalling, in contrast to Amer1 and Amer2, which are inhibitors, suggesting a nonredundant role of Amer proteins in the regulation of this pathway. Our data, together with those of previous studies, provide a comprehensive picture of similarities and differences within the Amer protein family.AMER3 physically interacts with APC by two hybrid (1, 2). AMER3 physically interacts with APC by anti tag coimmunoprecipitation (1, 2, 3). APC physically interacts with AMER3 by anti bait coimmunoprecipitation (View interaction). AMER3 physically interacts with APC, AMER1 and Conductin by anti bait coimmunoprecipitation (View interaction). AMER3 physically interacts with AMER1 by anti tag coimmunoprecipitation (1, 2). AMER3 and APC colocalize by fluorescence microscopy (View interaction). Conductin physically interacts with AMER3 by anti tag coimmunoprecipitation (View interaction). APC physically interacts with AMER2 by anti tag coimmunoprecipitation (View interaction). Conductin physically interacts with AMER3 by anti tag coimmunoprecipitation (1, 2). AMER1 and AMER3 colocalize by fluorescence microscopy (View interaction). APC physically interacts with AMER1 by anti tag coimmunoprecipitation (View interaction).
EVALuna2:10304